2024
DOI: 10.12997/jla.2024.13.1.53
|View full text |Cite
|
Sign up to set email alerts
|

Putative Pathogenic Variants of ABCG5 and ABCG8 of Sitosterolemia in Patients With Hyper-Low-Density Lipoprotein Cholesterolemia

Nobuko Kojima,
Hayato Tada,
Akihiro Nomura
et al.

Abstract: Objective Sitosterolemia is a rare autosomal recessive disease caused by the deleterious variants of adenosine 5'-triphosphate (ATP)-binding cassette sub-family G member 5 ( ABCG5 ) or ATP-binding cassette sub-family G member 8 ( ABCG8 ). There are only few data on the pathogenicity of ABCG5 and ABCG8 . This study aimed to propose a scheme for determining variant pathogenicity and to catalog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…To estimate the presence of deleterious ABCG5 or ABCG8 variant(s), it is useful to measure serum sitosterol levels. We have shown that a serum sitosterol level of 5 μg/mL or more is a useful “marker” for the presence of deleterious ABCG5 or ABCG8 variant(s) [ 63 ]. In addition, we can assume that patients whose serum sitosterol level is 10 μg/mL or more are highly likely to have sitosterolemia and have deleterious ABCG5 or ABCG8 variants in both alleles.…”
Section: Sitosterolemia As a Phenocopy Of Fhmentioning
confidence: 99%
“…To estimate the presence of deleterious ABCG5 or ABCG8 variant(s), it is useful to measure serum sitosterol levels. We have shown that a serum sitosterol level of 5 μg/mL or more is a useful “marker” for the presence of deleterious ABCG5 or ABCG8 variant(s) [ 63 ]. In addition, we can assume that patients whose serum sitosterol level is 10 μg/mL or more are highly likely to have sitosterolemia and have deleterious ABCG5 or ABCG8 variants in both alleles.…”
Section: Sitosterolemia As a Phenocopy Of Fhmentioning
confidence: 99%